Noise and the Perceptual Filling-in effect - Zomet, Ativ (Sci Rep, 2016)
Nearby collinear flankers increase the false alarm rate (reports of the target being present when it is not) in a Yes-No experiment. This effect has been attributed to “filling-in” of the target location due to increased activity induced by the flankers. According to signal detection theory, false alarms are attributed to noise in the visual nervous system. Here we investigated the effect of external noise on the filling-in effect by adding white noise to a low contrast Gabor target presented between two collinear Gabor flankers at a range of target-flanker separations. External noise modulates the filling-in effect, reducing visual sensitivity (d′) and increasing the filling-in effect (False Alarm rate). We estimated the amount of external noise at which the false alarm rate increases by the √2 (which we refer to as N(FA)). Across flank distances, both the false alarm rate and d′ (with no external noise) are correlated with N(FA). These results are consistent with the notion that nearby collinear flankers add both signal and noise to the target location. The increased signal results in higher d′ values; the increased noise to higher false alarm rates (the filling effect).